Social network characteristics associated with mid-to-older aged adults’ co-engagement in physical activity - Martin Anderson; Srebrenka Letina; Mark McCann; Jelena Milicev; Grace Dibben; Abi MacDonald; Kirstin Mitchell; Laurence Moore; Jonathan R. Olsen; Victoria J. Palmer; Benjamin P. Rigby; Sharon A. Simpson; et al. (PLoS ONE, 2025)
Objectives Physical activity is associated with a greater quantity and quality of social connections. Participating in physical activity with others (co-engagement) has dual physical and social benefits that can promote healthy ageing. We aimed to understand the social network characteristics of mid-to-older aged adults associated with co-engagement in physical activity. Methods Adults aged 55–75 years completed a social network survey (3679 social contacts reported by 140 participants). Multilevel modelling was used to identify the characteristics of participants, social contacts, and relationships that were predictive of co-engagement in physical activity. Results Network size and relationship quality were not associated with co-engagement. Similarity in age, greater interaction frequency, closer geographic proximity, and shorter relationship length were associated with higher odds of co-engagement. Discussion For co-engagement, the quality and quantity of relationships were less important than the convenience and accessibility of relationships, particularly newer relationships. As such, co-engagement ties can be understood as part of a dynamic social convoy which fulfil a specific function at a specific life stage. An understanding of naturally occurring tendencies for co-engagement may be utilised to identify leverage points for the development of interventions.